2019
DOI: 10.1016/j.ajoc.2019.100525
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral giant retinal pigment epithelial tears in hypertensive choroidopathy

Abstract: Purpose To report a case of hypertensive choroidopathy with bilateral bullous serous retinal detachments (SRDs), retinal pigment epithelial detachments (PEDs), and giant retinal pigment epithelial (RPE) tears. Observations A 68-year-old man with a history of hypertension and diabetes mellitus presented with bilateral visual loss of about 10 day's duration. He discontinued his oral medications for 2 months without the advice of a physician. At his first visit, the best-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…RPE tears outside the macula, as in this case, are very rare. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 In particular, there have been only a few reports of RPE tears after glaucoma filtering surgery, 2 , 3 , 4 the pathophysiology has not been clearly described and the appropriate treatment has not been established. In this report, we showed that hypotony is central to the development of this condition and that elevating IOP is essential for the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…RPE tears outside the macula, as in this case, are very rare. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 In particular, there have been only a few reports of RPE tears after glaucoma filtering surgery, 2 , 3 , 4 the pathophysiology has not been clearly described and the appropriate treatment has not been established. In this report, we showed that hypotony is central to the development of this condition and that elevating IOP is essential for the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Giant RPE rip has also been reported in patients with hypertensive choroidopathy. [ 7 8 ] The blood pressure of our patient was also high. However, unilateral presentation as well as the absence of other typical features such as retinal hemorrhages, hard exudates, disc edema, and exudative retinal detachment makes hypertensive choroidopathy in this patient unlikely.…”
Section: Discussionmentioning
confidence: 62%
“…4 Therefore, successful blood pressure management could contribute to the prompt resolution of exudative retinal detachment, as reported in previous cases. 8 In our case, several drugs were used to treat the aHUS and the hypertensive crisis. In particular, Eculizumab, which is a humanized monoclonal antibody against complement protein C5a.…”
Section: Discussionmentioning
confidence: 89%